Yeast hydrolysate as a functional anti-obesity ingredient: appetite suppressive effects of yeast hydrolysate in food-deprived mice - Hong, Ki Bae; Jung, Eun Young; Kim, Jae Hwan; Chang, Un Jae; Suh, Hyung Joo (Progress in Nutrition, 2015)
The aim of this study was to investigate the appetite suppression effects of yeast hydrolysate (YH). Male ICR mice (8 weeks old) were randomly divided into three groups (n=6) as follows: Saline group, which was treated with saline (control); YH0.5 group, which was treated with YH 0.5 g/kg BW; and YH1 group, which was treated with YH 1 g/kg BW. At the beginning of the experiment, the mice were intraperitoneally (IP) injected with either saline or YH. The results showed that YH caused a significant attenuation of food intake in fasted mice (p<0.05) and significantly lowered serum ghrelin levels (YH0.5, 2002.22 pg/mL; YH1, 2337.65 pg/mL vs. Saline, 3363.61 pg/mL, p<0.05). This study indicates that the appetite suppression effects of YH is likely explained by the attenuation of ghrelin.